Practical Approach to Criticality Assessment - Fuchs, Pavel; Kamenický, Jan; Zajíček, Jan; Soušek, Radovan (International Institute of Informatics and Systemics, 2018)
Throughout our career, while working in several different companies, it appeared apparent that every man has his own explanation of the term “criticality”, no matter if the company was from petrochemical, energy or automotive industry. Moreover, every man believes that his understanding of that term is the only correct one. Criticality is often used as the most important factor in the decision making process about maintenance strategy, spare parts purchases etc. There is currently no existing definition which can explain criticality in a general way, hence this paper was made to show the different points of view on this term. This paper presents the practical multi-criterion criticality approach and offers a solution of how to make calculations/evaluations of criticality more universal.
Praktický přístup k hodnocení kritičnosti
Keywords: Criticality, decision making process, maintenance optimization.; Kritičnost, rozhodovací proces, údržba, optimalizace